A STUDY ON THE SOCIAL NETWORK ANALYSES OF DIVE CENTERS AND SUSTAINABLE TOURISM DEVELOPMENT IN PEMUTERAN BALI, INDONESIA - Danis Arbabun NAJA; Slamet SUPRAYOGI; Muh Aris MARFAI; Djati MARDIATNO (Geo Journal of Tourism and Geosites, 2021)
The increasing interest of tourists over the last few decades in the Pemuteran Tourism Area has become a major challenge in its management and sustainability. The dive centers located in this area offer business services such as diving and snorkeling, which are the leading tourism activities in Pemuteran. These centers also experience various changes that are rel ated to business operations and conservation strategies. This study aims to (1) determine the characteristics of these centers in the Pemuteran marine tourism area, (2) analyze the network pattern between these centers in these areas, and (3) formulate a sustainable tourism developmental strategy. In addition, the study made use of a descriptive and qualitative research method. The data used was collected through semi-structured census interviews on the entire population of the dive centers in the Pemuteran marine tourism area. The results show that the collaboration network between dive centers in Pemuteran is a centralized collaboration. Furthermore, this collaboration occured in both operational and conservational activities. The nationality of the owner and the year in which the centers were established, are factors that influence the collaboration of dive centers in Pemuteran. Conclusively, optimizing the role of the government, and the involvement of local communities around Pemuteran is an important task needed in developing sustainable Pemuteran diving tourism.